Outsourcing and In-Sourcing of Innovation in Network Organizations - ZARAYCHENKO, Irina A.; SHINKEVICH, Aleksey I.; MITROFANOVA, Marina Yu.; LADYKOVA, Tatiana I.; NURETDINOVA, Yuliya V.; KHARISOVA, Guzyal M.; ZHUKOVA, Marina A. (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The development of open innovation’s concept, along with the growing demands of the environment, gives rise to new and unique forms of management, which ensure long-term development of economic systems both at the micro- so at the macro-level. The development of the network economy, capital limitations of separate business units leads to a need to build business models based on flexible network forms of interactions. At the same time the problem of limited resources of network organizations creates the need to form various associations, to lead certain types of innovative activities to outsourcing and focus on maximizing the benefits of core competencies. The article deals with the specifics of innovation networks’ construction based on their two-level nature: the level of actors and artifacts. At the same time the economic role of innovation rents is revealed at the stage of construction and development of innovative network through justifying the selection of engagement strategies (outsourcing, in-sourcing, Alliance).